Silicato de alumínio como manejo alternativo de plantas daninhas - Rodrigo Magalhaes Faria (2017)
With the frank growth of industrialization also increases the amount of waste generated. Mining companies are examples of major waste stations. In many cases, these wastes have a high polluting potential, which creates the risk of environmental pollution. Therefore, studies that evaluate ways to dispose of these wastes safely to the environment are of paramount importance. In this sense, the objective of this work was to elucidate the impact of the application of aluminum silicate on the emergence of weeds. The experiment was conducted in greenhouse in pots with a volume of 5 dm³ in the agricultural year 2015/2016 in the city of Montes Claros - MG. The experimental design was a randomized complete block design in a 4x2 + 1 factorial scheme that corresponded to 4 doses of aluminum silicate, 2 application methods and an additional treatment without application of aluminum silicate with 4 replicates, making up 36 experimental units. The number of emerged seedlings was counted at 7 and 20 days after emergence and these were classified according to family and species. With these data it was possible to carry out a phytosociological survey from which several indexes were calculated, among them the index of importance value and the coefficient of similarity. Twenty days after emergence, the aerial part of the plants was collected to evaluate the accumulation of fresh and dry matter. The aluminum silicate altered the emergence of weeds. When applied on surface, as the dose of aluminum silicate was increased the number of individuals, the amount of species and the accumulation of fresh and dry matter reduced. The physical barrier of aluminum silicate affected all the studied species, consequently the IVIs and coefficients of similarity have also changed. The species with small and positive photoblastic seeds were the most affected, as is the case of Amaranthus spinosus, Portulaca oleracea that practically did not emerge at the doses of 180 and 240 t ha-1. When the aluminum silicate was incorporated, the emergence was stimulated and germinated more seedlings in these treatments than in the absent witnesses of application of this residue. It is concluded that from the dose of 60 ton ha-1 the surface aluminum silicate reduces the emergence of seedlings, while the provision of this residue incorporated in the soil stimulates the emergence which generates the possibility of destination of this residue in agricultural soils.